Live music, liquor and the city: An examination of the influence of liquor regulation on place-specific live music activity - Ballico, Christina (2016)
Live music plays a central role in the cultural life of cities. It provides an enticing entertainment option for the public, while culturally enhancing the spaces within which it operates. Broadly, the cultural and creative pulse of a city can be determined by its locally-focused and engaged live music scene: the breadth of genres being performed, and the vibrancy, number, and clustering of live music venues. The ways in live music activity is facilitated varies from locale to locale, being influenced by a range of cultural attitudes and regulatory factors, which in turn determine the ways in, and circumstances under, which such activity can and cannot occur.  This paper examines the tensions at play between place-specific live music activity and regulation that pertains to the live music sector. It reports on research undertaken in Perth, Western Australia (WA), and places a specific focus on liquor regulation which primarily governs the spaces in which the majority of regular locally-focused live music occurs. As this paper argues, despite a range of initiatives in place to lift the creative and cultural identity of the city, much of this has failed to engage with the live music sector. In turn, and due in part to regulation which does not, in-situ, address the varying needs of the sector, it is limited in its ability be recognised as making a vital contribution to the city’s creative and cultural identity.